Surface Modification and Heat Generation of FePt Nanoparticles - Da-Hua Wei (Materials, 2017)
The chemical reduction of ferric acetylacetonate (Fe(acac)3) and platinum acetylacetonate (Pt(acac)2) using the polyol solvent of phenyl ether as an agent as well as an effective surfactant has successfully yielded monodispersive FePt nanoparticles (NPs) with a hydrophobic ligand and a size of approximately 3.8 nm. The present FePt NPs synthesized using oleic acid and oleylamine as the stabilizers under identical conditions were achieved with a simple method. The surface modification of FePt NPs by using mercaptoacetic acid (thiol) as a phase transfer reagent through ligand exchange turned the NPs hydrophilic, and the FePt NPs were water-dispersible. The hydrophilic NPs indicated slight agglomeration which was observed by transmission electron microscopy images. The thiol functional group bond to the FePt atoms of the surface was confirmed by Fourier transform infrared spectroscopy (FTIR) spectra. The water-dispersible FePt NPs employed as a heating agent could reach the requirement of biocompatibility and produce a sufficient heat response of 45 °C for magnetically induced hyperthermia in tumor treatment fields.